PENERAPAN METODE CRITICAL PATH METHOD (CPM) DAN PRECEDENCE DIAGRAM METHOD (PDM) DALAM RESCHEDULLING PROYEK KONSTRUKSI (Studi Kasus: Kegiatan Peningkatan Jalan Poros Wawonggole – Palarahi) - Asman Asman; Edwar Ngii; Adris Ade Putra (Jurnal Manajemen Rekayasa (Journal of Engineering Management), 2021)
In the implementation of an activity, sometimes there are obstacles or obstacles that can affect the time of work implementation, such as unpredictable weather conditions that have an impact on delays in implementing project activities. The challenge in project implementation is how to plan an effective time schedule and cost efficient planning without reducing quality. In the construction industry there are several project scheduling methods known, including: Bar Chart, Network Diagram (CPM, PDM). The purpose of this research is to find the method of planning and project scheduling that is commonly used in Indonesia, to compare each method of planning and project scheduling to find a character that matches the nature of the project, and to simulate the project planning and scheduling method and to analyze its strengths and weaknesses. Data collection is done by collecting data on the improvement of the Wawonggole - Palarahi axis road, namely in the form of the Bar Chart method which is converted into the form of the CPM, PDM, and Time Chainage Diagram methods.The result of this research is that the rescheduling duration is 20 days, there is a variance of 88.89% of the duration of the plan, for direct costs there is a reduction of 39.28% and for indirect costs there is an increase consisting of 10% profit and 5% overhead. For the total RAB as a whole after rescheduling is reduced by 60.72% of the planned RAB from the initial budget plan or Rp. 3. 189. 484. 250, 57. on the implementation of the Wawonggole-Palarahi Poros Road Improvement activities.Keywords: Project Scheduling, Network Diagram, Microsoft Project 2016